Detection of Paenibacillus larvae by Real-Time PCR - Sérgio Salla Chagas (Acta Scientiae Veterinariae, 2010)
Paenibacillus larvae is the agent of the American Foulbrood disease (AFB), which may determine the death of the hive. The detection strategy for its diagnosis is based on clinical signs of disease, isolation and identification of P. larvae, which usually employs microbiological and biochemical methods. Recently, molecular methods based on analysis of 16S rDNA by conventional PCR have been adopted, providing greater security and analytical speed. The rapid diagnosis is important to minimize economic losses and assess routes of spread of the pathogen. Despite the strong existing sanitary control, P. larvae was recently identified in the Brazilian states of Rio Grande do Sul and Paraná. After that, outbreaks have been reported in neighboring countries. This investigation was conducted to develop a protocol for detection of P. larvae by real-time PCR, allowing the reduction in the time of diagnosis, without loss of robustness found in the conventional PCR methods. Materials, Methods & Results: Twenty-nine (29) P. larvae strains were evaluated by real-time PCR using SYBR Green. The primers Pltr-F/R were designed according to the sequence X60619 of 16S rDNA gene published in GenBank, to amplify a fragment of 74 base pairs. The target gene is highly conserved and specific to P. larvae. The amplification conditions consisted of 1 cycle of 50°C for 2 min and 1 cycle of 95°C for 10 min, followed by 40 cycles of 95°C for 15 s and 60°C for 1 min. The fluorescence was monitored during the annealing at 60°C. The reactions were conducted in a 7500 Real Time PCR System equipment, using SYBRGreen PCR master mix (both Applied Biosystems), containing 2X Platinum SYBRGreen qPCR Supermix-UDG. The concentrations of primers were 1, 10 and 100 mM, and different concentrations of MgCl2 (0,0 mM de MgCl2, 1.0 mM de MgCl2, 2.0 mM de MgCl2 and 3.0 mM de MgCl2) were tested, with a final volume of 50 mL; 25 mL and 15 mL, containing a 5 mL sample. The analysis of the melting curve was made based on a 95°C for 15 s and 60°C for 20 s and one cycle with temperature ranging between 60°C and 95°C for 20 min. The best results of sensitivity and specificity in the reaction with SYBR Green were obtained with primer concentration set as 100 mM. The different concentrations of MgCl2 tested did not affect the performance of the reaction. No amplification was observed with DNA obtained from Paenibacillus alvei or Bacillus species. The limit of detection was set as 6 pg of DNA template. The regression analysis of the CT values of the PCR products showed a linear relationship between the initial amounts of DNA template and the values of CT (R2 = 0.9982), indicating that the test is highly precise. Discussion: The protocol developed allowed the unequivocal identification of P. larvae, as all strains were detected by this approach. The amplification of the expected 16S rDNA gene fragment was verified by amplification with the primers Pltr F/R only for chromosomal DNA of P. larvae. In addition,